TREATMENT OF CHRONIC TONSILLITIS WITH THYMOGEN SPRAY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
During the study, 30 patients and 30 volunteer workers were selected for the control group, who applied to the ENT polyclinic of the Tashkent Medical Academy . The diagnosis of the disease is based on general and local symptoms, patient complaints, medical history, and results of laboratory tests. Pathological microflora were found in the obtained smears. Improvement of treatment methods for chronic tonsillitis was developed.